Inovasi Media Pembelajaran Berbasis Website dengan Pendekatan PjBL untuk Meningkatkan Kompetensi Routing Static pada Siswa Kelas XI TKJ (Studi Kasus: SMK Negeri 1 Sidayu Kabupaten Gresik) - Setiawan, Fauzi; Susanti, Martini Dwi Endah (IT-Edu : Jurnal Information Technology and Education, 2025)
In the 21st century, the development of information technology has made it easier to access information and supports the automation of routine activities as well as communication that can be done from anywhere. In the field of education, teachers are required to design learning media that keep up with the times. Learning media based on information technology, such as learning applications, are developed to help teachers deliver material more effectively. With that background, the researchers conducted a study aimed at developing and producing web-based learning media and analyzing its impact on improving students' static routing competence in the cognitive aspect of the Network Infrastructure Administration subject. This learning media is designed by applying the Project Based Learning model. The research was conducted using the Research and Development (R&D) method with the ADDIE development model. The trial design used is the One Group Pretest-Posttest Design. The research data was taken from the XI TKJ 1 class students at SMK Negeri 1 Sidayu, with a total of 35 participants, and involved several expert validators, including lecturers and teachers. The research results show that the validation of learning media reached a value of 96.36% (very valid), material validation 86% (very valid), test question validation 90% (very valid), and RPP validation 80.85% (valid). Hypothesis test analysis resulted in sig. (2-tailed) = 0.001, where 0.001 < 0.05, thus H0 is rejected and H1 is accepted. This indicates a significant effect of using website-based learning media with the Project Based Learning model on students' static routing competence. Based on the test results, it can be concluded that website-based learning media using the Project Based Learning model effectively improves students' static routing competence. Keywords: Learning Media, Project Based Learning, Static Routing, Website